Brazilian civil society and South–South cooperation: countering the Green Revolution from abroad - Trajber Waisbich, L; Cabral, L (Institute of Development Studies, 2023)
Having transformed its hinterland to become a major exporter of agricultural commodities, Brazil has, since the mid-2000s, set up a range of South–South cooperation (SSC) initiatives to export its agri-food policies and technologies to othe countries, mainly in Latin America and sub-Saharan Africa. Both the domestic agricultural policies and SSC have been scrutinised and shaped by interactions with civil society actors, from peasant associations and trade unions to rights-based non-governmental organisations. This article explores modes of interaction and interdependence between different civil society and state actors in the context of SSC relating to food security and agricultural development. It analyses changes and continuities in civil society engagement, and mobilisation and de-mobilisation dynamics. Recently, the government’s de-prioritisation of the South–South agenda has been accompanied by very limited civil society activism. The article discusses why this needs attention and the challenges that need to be considered to reinstate productive state–civil society dynamics.